2013
DOI: 10.4274/jcrpe.1072
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resistin Serum Concentrations in Patients with Type 1 Diabetes Mellitus

Abstract: Objective: Adiponectin, leptin, and resistin are adipokines which play a significant role in the regulation of lipid and carbohydrate metabolism in patients with type 2 diabetes, while little is known about their role in type 1 diabetes mellitus (T1DM). The aim of this study was to measure serum adiponectin, leptin, and resistin levels and to investigate their relationships with some parameters in patients with T1DM and healthy controls.Methods: Fifty children and adolescents with T1DM (21 boys and 29 girls) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Leptin is known as a key appetite-regulating hormone. Recent studies revealed that leptin has the effect of normalizing hyperglycemia and increasing insulin sensitivity [ 17 ]. The leptin data of patients with T1DM compared with healthy controls are controversial, especially during pubertal development [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin is known as a key appetite-regulating hormone. Recent studies revealed that leptin has the effect of normalizing hyperglycemia and increasing insulin sensitivity [ 17 ]. The leptin data of patients with T1DM compared with healthy controls are controversial, especially during pubertal development [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adipokines such as adiponectin, leptin and resistin are bioactive mediators secreted by adipose tissue [ 6 ]. They have a significant role in the regulation of lipid and carbohydrate metabolism and involvement in the inflammatory responses [ 7 ]. In contrast to type 2 diabetes, involvement of adipose tissue in the low-grade systemic inflammation observed in T1DM has been investigated far less.…”
Section: Introductionmentioning
confidence: 99%
“…Although resistin is considered as an adypocytokine, a translational study by Schwartz and Lazar implied that human resistin primarily originates from macrophages, rather than from adipocytes [4]. Increased resistin concentrations are commonly seen in diabetes mellitus, metabolic syndrome, and inflammatory bowel disease [5][6][7], but previous studies have also shown that elevated resistin levels are associated with the increased risk for development of CRC [8]. Resistin is believed to contribute to cancer expansion by stimulating malignant cell growth and proliferation, but the experiments conducted in order to verify this hypothesis yielded contradictory results [9].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, controversial results on the role of resistin in the development of IR, T2D and metabolic syndrome are described ( 63 , 64 , 69 ). Increased circulating levels are also reported in T1D subjects ( 70 ). A SNP in resistin promoter is, in addition to obesity, also associated with T2D ( 71 ).…”
Section: Resistinmentioning
confidence: 91%